PERAN EVENT DALAM PEMBENTUKAN CITRA REDLINE MANAGEMENT & TALENT SCHOOL - Siswanto, Yulita Puspitasari, Dian Esti Nurati & (Transformasi, 2017)
This research entitled The Role Of Event In the Formation of Image at Redline Management &Talent School. Perception expressed by some people if the modelling world as closely identifiedwith negative life, like glamour and popularity was always being priority. This factor makingRedline Management & Talent School motivated to establish the school and talent agency thatfocuses on developing talent and character through the role of event. The purpose of thisresearch was to determine how the role of event in the formation of image at redlinemanagement & talent school.Keywords : Public Relation and Company’s Image